(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Today’s modern industry and trade, internet evaluations matter a lot. Buying web items is often influenced by the opinions of other customers. Because of this, unscrupulous folks or organisations attempt to rig customer evaluations to their personal advantage. Using a lodging rating database, this research examines the performance of semi-supervised (SSVD) and supervised (SVD) word extraction methods for detecting false ratings.